Fiscal Decentralization and Governance : A Cross-Country Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Based on cross-country data for up to 78 countries, this paper shows that fiscal decentralization-the assignment of expenditure and revenue mobilization functions to subnational levels of government-is associated with various indicators of governance, such as corruption, rule of law, and government effectiveness. Unlike previous studies in the decentralization/governance literature, which focus primarily on expenditure-based measures of decentralization, the results reported in this paper show that the relationship between decentralization and governance depends on how subnational expenditures are financed. The higher the share in total subnational revenues of nontax revenues and grants and transfers from higher levels of government, the stronger the association between decentralization and governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet